Early Christian Latin poets - White, Carolinne (Early church fathers., 2000)
"This is the first substantial overview of the Golden Age of Christian Latin poetry, from the fourth to sixth centuries." "Carolinne White's study sets the works in their literary and historical context, and shows how these poets were motivated by a desire to convey the truth of the Christian message. Questions of form and content, continuity with classical culture, theological issues and contemporary heresies are all explored, prior to clear, sensitive translations of over thirty poems and excerpts, many of which have never before been translated into English."--Jacket